2020
DOI: 10.1155/2020/8885865
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Tocols to Food Sensorial Properties, Stability, and Overall Quality

Abstract: This paper reviews the contribution of tocopherols and tocotrienols (tocols) to food quality as well as their bioactivity and health-promoting properties, which have attracted researchers and food technologists. Tocols are lipophilic phenolic antioxidants encompassing tocopherols that are characterized by a saturated side chain and tocotrienols with an unsaturated isoprenoid side chain. Tocols are natural constituents of several foods like dairy, vegetable oils, nuts, and grains. Their presence in foods, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In addition, these authors have reported a good capacity of DPSO in the protection against UV light and therefore against cellular damage. Other studies revealed that date seed oils are good sources of α-tocotrienol [4], which is reported as an effective compound to reduce the breast cancer risk [5,6], cholesterol, and low-density lipoprotein cholesterol in humans [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these authors have reported a good capacity of DPSO in the protection against UV light and therefore against cellular damage. Other studies revealed that date seed oils are good sources of α-tocotrienol [4], which is reported as an effective compound to reduce the breast cancer risk [5,6], cholesterol, and low-density lipoprotein cholesterol in humans [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to the EFSA (European Food Safety Authority), the average α -tocopherol absorption from a usual diet is about 75%, which is 13 mg/day for men, 11 mg/day for women, and 9 mg/day for children of both sexes aged 3 to <10 years and 6 mg/day if aged <3 years [ 48 ]. Vitamin E bioavailability is influenced by various factors, such as gender, age, and genotype, as well as environment factors, food habits, and lifestyle [ 49 ]. In terms of absorption, α -tocopherol is more assimilated by our body because α -TTP (alpha-tocopherol transfer protein) is a liver cytosolic transport protein that facilitates α -tocopherol ( α -T) transfer.…”
Section: Resultsmentioning
confidence: 99%
“…The tocols known as naturally occurring compounds in oils indicate the oil quality, stability, origin, or nutritional values. They may also provide additional consumer health advantages in disease prevention due to their anti-oxidative and vitamin E activity (Delgado et al, 2020). Moreover, these compounds are used as lipid stabilizers in several food industries.…”
Section: Tocopherols (-T) and Tocotrienols (-Tt) Profilementioning
confidence: 99%